Cassava biotechnology priority setting: old hat for a new tool - Henry, Guy; Thro, Ann Marie; Lynam, John K. (International Center for Tropical Agriculture, 1995)
Biotechnology techniques, tools and products can offer time and cost savings for agricultural R & D. Biotech`s early start concentrated for the major part on highly commercial, primary crops and private sector labs. Biotech research involvement in a secondary crop like cassava has been relatively recent. The Cassava Biotechnology Network (CBN) was founded to optimize the utilization of scarce cassava biotech resources while enhancing the direct and indirect impact of cassava biotechnology. CBN therefore has emphasized the role of Priority setting as one of its tools to accomplish these objectives. CBN offers an opportunity for reassessing current cassava research needs and subsequent priorities. The reassessment will include a socioeconomic, political, and institutional assessment of the comparative advantages of biotechnology research over traditional research approaches. Biotechnology does not require a special process at the needs assessment, user interaction stage. Only at a later stage, when biotechnology is one of possible approaches to an identified need, is a method required for objective consideration among research approaches. The final product must be a user-friendly decision making tool. Any priority setting method is of value only if it is dynamic and flexible